A Synthesis of Viral Contribution to Marine Nitrogen Cycling - Wang, Shuai; Yang, Yu; Jing, Jiaojiao (Frontiers in Microbiology, 2022)
Nitrogen is an essential component of major cellular macromolecules such as DNA and proteins. Its bioavailability has a fundamental influence on the primary production of both terrestrial and oceanic ecosystems. Diverse marine microbes consume nitrogen, while only a limited taxon could replenish it, leaving nitrogen one of the most deficient nutrients in the ocean. A variety of microbes are involved in complex biogeochemical transformations of nitrogen compounds, and their ecological functions might be regulated by viruses in different manners. First and foremost, viruses drive marine nitrogen flow via host cell lysis, releasing abundant organic nitrogen into the surrounding environment. Secondly, viruses can also participate in the marine nitrogen cycle by expressing auxiliary metabolic genes (AMGs) to modulate host nitrogen metabolic pathways, such as nitrification, denitrification, anammox and nitrogen transmembrane transport. Additionally, viruses also serve as a considerable reservoir of nitrogen element. The efficient turnover of viruses fundamentally promotes nitrogen flow in the oceans. In this review, we summarize viral contributions in the marine nitrogen cycling in different aspects and discuss challenges and issues based on recent discoveries of novel viruses involved in different processes of nitrogen biotransformation.